Benzimidazole micromolecule-based proton exchange composite membrane for electrolyzed water and preparation method thereof

By adding sulfonated benzimidazole small molecules as fillers to the polymer matrix, the proton conductivity and mechanical properties of the proton exchange membrane are improved, the temperature and cost limitations of the existing membrane are solved, and the chemical attacks are enhanced Stability extends the battery life.

CN119144115APending Publication Date: 2024-12-17CHANGZHOU UNIV
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411283410.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing proton exchange membranes have limitations in operating temperature and cost, and are vulnerable to chemical attacks to lead to degradation, affecting the working efficiency and service life of the battery.

Method used

Using a proton exchange composite membrane based on benzimidazole small molecules, the proton conductivity and mechanical properties are improved by adding sulfonated benzimidazole small molecules (SHPBI) to the polymer matrix, and the anti-swelling performance is enhanced through ionic cross-linking. and oxidative stability.

Benefits of technology

It improves the proton conductivity and mechanical properties of the membrane, reduces costs, and enhances the stability of chemical attacks, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144115A_ABST
    Figure CN119144115A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of polymer electrolyte membranes, and particularly relates to a benzimidazole micromolecule-based proton exchange composite membrane for electrolyzing water and a preparation method thereof. The preparation method comprises the following steps: firstly synthesizing 5, 5 '-bis [2-(2-hydroxy-5-sulfophenyl) benzimidazole], then synthesizing sulfonated polyetheretherketone, and finally preparing the proton exchange composite membrane based on benzimidazole micromolecules. The benzimidazole rigid rod-like micromolecules with sulfonic acid groups are designed and prepared by utilizing the advantages of heat resistance, acid resistance, alkali resistance and better dissolvability than PBI of the benzimidazole micromolecules, and the benzimidazole rigid rod-like micromolecules are added into a polymer matrix as a filler to prepare the composite membrane, so that the proton conductivity, the swelling resistance and the oxidation stability of the original polymer membrane are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer electrolyte membranes, and in particular relates to a proton exchange composite membrane based on benzimidazole small molecules for electrolysis of water and a preparation method thereof. Background Art

[0002] Green hydrogen production, i.e. the electrolysis of water using renewable electricity, is gaining increasing attention. The required electricity is generated by renewable energy sources (RES), such as wind, hydro or solar. Green hydrogen is climate neutral, as neither the production process nor the end product of hydrogen and oxygen harms the environment. Therefore, the development of electrolysis technology is a research topic.

[0003] Proton exchange membrane (PEM) water electrolysis technology is considered to be the most promising technology for the sustainable production of green hydrogen from water and intermittent renewable energy. In addition, PEM water electrolysis also has the advantages of compact system design, high operating current density, high hydrogen purity, high energy efficiency, and fast response speed. Proton exchange membranes mostly use perfluorosulfonic acid membranes, the most common of which is Nafion. Subsequently, some people have also developed a short-chain perfluorosulfonic acid membrane Aquivion. However, these Membranes have limitations in operating temperature and are expensive.

[0004] Therefore, some researchers are actively developing cost-effective hydrocarbon polymer membranes to overcome the limitations of PEM water electrolysis membranes. To maintain the stability of hydrocarbon membranes in oxygenated PEMWE, sulfonated polymers have been studied. The introduction of negatively charged sulfonated groups can prevent polymer chain breakage from the main chain structure and side reactions, and improve proton transport by providing large hydrophilic domains.

[0005] Sulfonated polymer is a substance that can replace Nafion membrane. Among them, sulfonated polyetheretherketone (SPEEK) shows a structure similar to Nafion membrane, but its high sulfonic acid ratio will cause it to swell after absorbing excessive water, resulting in a decrease in mechanical properties. In order to solve this problem, SPEEK composite membrane is formed by adding inorganic fillers, ionic liquids, heteropoly acids, etc. to SPEEK, so that it has high mechanical strength and thermal stability while meeting high proton conductivity. However, this type of proton exchange membrane is susceptible to chemical attacks by hydroxyl and peroxyl radicals, causing degradation of the proton exchange membrane, seriously affecting the working efficiency and service life of the battery. Summary of the invention

[0006] The present invention utilizes the advantages of benzimidazole small molecules being heat-resistant, acid-resistant and alkali-resistant, and having better solubility than PBI, and designs and prepares benzimidazole rigid rod-shaped small molecules with sulfonic acid groups, and adds them into a polymer matrix as fillers to prepare a composite membrane, thereby improving the proton conductivity of the original polymer membrane and improving its mechanical properties. To achieve the above objectives, the preparation steps of the proton exchange composite membrane are as follows:

[0007] (1) Preparation of sulfonated benzimidazole small molecule (SHPBI)

[0008] 3,3'-diaminobenzidine and 5-sodium sulfosalicylate dihydrate are used as reaction raw materials, and polyphosphoric acid is used as solvent. Under nitrogen atmosphere, the residual oxygen in polyphosphoric acid is removed under mechanical stirring at above 80°C, and then the two raw materials are added in sequence, and the temperature is raised to 120°C after complete dissolution, and the reaction is continued for 3 hours, and then the temperature is raised to 150°C, and the reaction is continued for 15 hours until the reaction solution changes color, and the reactant is poured into deionized water to cool and solidify, stirred with a glass rod, and washed by centrifugation with deionized water to make the washing water neutral, and then the remaining solid is placed in an oven for drying to obtain 5,5'-bis[2-(2-hydroxy 5-sulfophenyl)benzimidazole], which is named SHPBI.

[0009] The molar ratio of 5-sulfosalicylic acid sodium dihydrate to 3,3'-diaminobenzidine is greater than 2:1.

[0010] The amount of polyphosphoric acid used is greater than 10 times the total weight of the monomers.

[0011] The prepared benzimidazole small molecule with sulfonic acid group (SHPBI) has the following structural formula:

[0012]

[0013] (2) Preparation of sulfonated polyetheretherketone (SPEEK)

[0014] The dried PEEK was dissolved in concentrated sulfuric acid and stirred at 50 °C for 8 h, then the solution was slowly poured into an ice-water bath, the precipitated SPEEK was washed several times with deionized water, and then vacuum dried at 60 °C for 24 h to obtain the final product.

[0015] The mass volume ratio of PEEK to concentrated sulfuric acid is: 1g:10ml.

[0016] (3) Film formation

[0017] The prepared small molecule benzimidazole SHPBI and SPEEK were dissolved in dimethyl sulfoxide to form a uniform mixed solution, and the mixed solution was dropped onto a flat glass plate and placed in an oven at 60° C. to dry into a film.

[0018] The doping amount of SHPBI accounts for 5-15% of the total mass of SHPBI and SPEEK.

[0019] The structural formula of the prepared proton exchange composite membrane is shown below:

[0020]

[0021] The proton exchange composite membrane based on benzimidazole small molecules prepared by the present invention can be used as a proton exchange membrane for electrolyzing water.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] (1) Adding organic filler SHPBI to sulfonated polyetheretherketone introduces more sulfonic acid groups into the membrane, further improving the proton conductivity of the membrane. And through the ionic crosslinking between small molecule SHPBI and SPEEK, the anti-swelling performance and oxidation stability of the composite membrane are effectively improved.

[0024] (2) SHPBI is resistant to acid, alkali and high temperature and has good solubility. Compared with inorganic fillers and metal oxide fillers, it will not agglomerate and cause a decrease in the mechanical properties of the membrane.

[0025] (3) Simple preparation process, good film-forming performance and low cost. The present invention uses a sulfonated polyetheretherketone polymer material that is cheaper than Nafion as a matrix, and prepares a sulfonated polyetheretherketone-sulfonated benzimidazole composite membrane by a solution casting method. The entire preparation process is simple and the membrane making cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 For SHPBI 1 HNMR spectrum.

[0027] Figure 2 This is a graph showing the change in proton conductivity of proton exchange composite membranes with different SHPBI doping amounts as a function of temperature.

[0028] Figure 3 Polarization curves of proton exchange composite membrane with SHPBI doping content of 10% for hydrogen production by electrolysis of water at different temperatures. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with specific embodiments.

[0030] Example 1

[0031] 30 g of polyphosphoric acid was weighed and added to a flask equipped with a stirrer and an air guide tube. Nitrogen was introduced and stirred at 80°C to remove residual air in the polyphosphoric acid. Then 1.07 g of 3,3'-diaminobenzidine and 2.65 g of sodium 5-sulfosalicylate dihydrate were added. The temperature was raised to 120°C and reacted for 3 hours. The temperature was then raised to 150°C and the reaction was continued for 15 hours. The reacted solution was then poured into ice deionized water for cooling, and then centrifuged and washed with deionized water until the pH was neutral. The obtained solid was placed in a vacuum oven at 80°C and dried for 24 hours. The obtained solid was named SHPBI.

[0032] 10 g of dry PEEK was dissolved in 100 ml of concentrated sulfuric acid, stirred at 80 °C for 3 h, and then the solution was slowly poured into ice deionized water. The precipitated polymer was washed with deionized water until the solution was neutral, and then vacuum dried at 60 °C for 24 h to obtain the final product SPEEK.

[0033] 0.188 g of SPEEK and 0.012 g of SHPBI were weighed and dissolved in 8 ml of DMSO to form a uniform mixed solution. The mixed solution was dropped onto a flat glass plate and dried in an oven at 60° C. for 24 h to obtain SPEEK / SHPBI-6%.

[0034] The mechanical strength of the prepared PEM in the wet state is 35.1 MPa, the swelling degree is 8% at 80 °C, and the conductivity is 41.5 mS cm -1 The remaining weight after treatment with Fenton's reagent was 95.1% (oxidation stability); the prepared PEM was made into a membrane electrode (anode catalyst: IrO2, cathode catalyst: Pt / C), and the PEM water electrolysis test was carried out (40°C, electrolyte: pure water), and the efficiency of hydrogen production by water electrolysis reached 32%.

[0035] Example 2

[0036] SPEEK and SHPBI were prepared in the same manner as in Example 1.

[0037] 0.184 g of SPEEK and 0.016 g of SHPBI were weighed and dissolved in 8 ml of DMSO to form a uniform mixed solution. The mixed solution was dropped onto a flat glass plate and dried in an oven at 60° C. for 24 h to obtain SPEEK / SHPBI-8%.

[0038] The mechanical strength of the prepared PEM in the wet state is 38.3 MPa, the swelling degree is 7.5% at 80 °C, and the conductivity is 46.3 mS cm -1The remaining weight after treatment with Fenton's reagent was 95.6% (oxidation stability); the prepared PEM was made into a membrane electrode (anode catalyst: IrO2, cathode catalyst: Pt / C), and the PEM water electrolysis test was carried out (40°C, electrolyte: pure water), and the efficiency of hydrogen production by water electrolysis reached 35%.

[0039] Example 3

[0040] SPEEK and SHPBI were prepared in the same manner as in Example 1.

[0041] 0.18 g of SPEEK and 0.02 g of SHPBI were weighed and dissolved in 8 ml of DMSO to form a uniform mixed solution. The mixed solution was dropped onto a flat glass plate and dried in an oven at 60° C. for 24 h to obtain SPEEK / SHPBI-10%.

[0042] The mechanical strength of the prepared PEM in the wet state is 40.4 MPa, the swelling degree is 7.0% at 80 °C, and the conductivity is 54 mS cm -1 The remaining weight after treatment with Fenton's reagent was 96.2% (oxidation stability). The prepared PEM was made into a membrane electrode (anode catalyst: IrO2, cathode catalyst: Pt / C) and the PEM water electrolysis test was carried out (40°C, electrolyte: pure water). -2 The minimum voltage reaches 7.0V at the current density, and the efficiency of hydrogen production by electrolysis of water reaches 40%.

[0043] Example 4

[0044] SPEEK and SHPBI were prepared in the same manner as in Example 1.

[0045] 0.176 g of SPEEK and 0.024 g of SHPBI were weighed and dissolved in 8 ml of DMSO to form a uniform mixed solution. The mixed solution was dropped onto a flat glass plate and dried in an oven at 60° C. for 24 h to obtain SPEEK / SHPBI-12%.

[0046] The mechanical strength of the prepared PEM in the wet state is 37.2 MPa, the swelling degree is 7.0% at 80 °C, and the conductivity is 47.1 mS cm -1 The remaining weight after treatment with Fenton's reagent was 96.5% (oxidation stability); the prepared PEM was made into a membrane electrode (anode catalyst: IrO2, cathode catalyst: Pt / C), and the PEM water electrolysis test was carried out (40°C, electrolyte: pure water), and the efficiency of hydrogen production by water electrolysis reached 36%.

[0047] Example 5

[0048] SPEEK and SHPBI were prepared in the same manner as in Example 1.

[0049] 0.172 g of SPEEK and 0.028 g of SHPBI were weighed and dissolved in 8 ml of DMSO to form a uniform mixed solution. The mixed solution was dropped onto a flat glass plate and dried in an oven at 60° C. for 24 h to obtain SPEEK / SHPBI-14%.

[0050] The mechanical strength of the prepared PEM in the wet state is 33.6 MPa, the swelling degree is 7% at 80 °C, and the conductivity is 42 mS cm -1 The remaining weight after treatment with Fenton's reagent was 96.7% (oxidation stability); the prepared PEM was made into a membrane electrode (anode catalyst: IrO2, cathode catalyst: Pt / C), and the PEM water electrolysis test was carried out (40°C, electrolyte: pure water), and the efficiency of hydrogen production by water electrolysis reached 33%.

[0051] Example 6

[0052] SPEEK and SHPBI were prepared in the same manner as in Example 1.

[0053] 0.19 g of SPEEK and 0.01 g of SHPBI were weighed and dissolved in 8 ml of DMSO to form a uniform mixed solution. The mixed solution was dropped onto a flat glass plate and dried in an oven at 60° C. for 24 h to obtain SPEEK / SHPBI-5%.

[0054] The mechanical strength of the prepared PEM in the wet state is 32.7 MPa, the swelling degree is 8% at 80 °C, and the conductivity is 38.1 mS cm -1 The remaining weight after treatment with Fenton's reagent was 94.5% (oxidation stability); the prepared PEM was made into a membrane electrode (anode catalyst: IrO2, cathode catalyst: Pt / C), and the PEM water electrolysis test was carried out (40°C, electrolyte: pure water), and the efficiency of hydrogen production by water electrolysis reached 28%.

[0055] Example 7

[0056] SPEEK and SHPBI were prepared in the same manner as in Example 1.

[0057] 0.17 g of SPEEK and 0.03 g of SHPBI were weighed and dissolved in 8 ml of DMSO to form a uniform mixed solution. The mixed solution was dropped onto a flat glass plate and dried in an oven at 60° C. for 24 h to obtain SPEEK / SHPBI-15%.

[0058] The mechanical strength of the prepared PEM in the wet state is 30.2 MPa, the swelling degree is 7% at 80 °C, and the conductivity is 38 mS cm -1The remaining weight after treatment with Fenton's reagent was 96.9% (oxidation stability); the prepared PEM was made into a membrane electrode (anode catalyst: IrO2, cathode catalyst: Pt / C), and the PEM water electrolysis test was carried out (40°C, electrolyte: pure water), and the efficiency of hydrogen production by water electrolysis reached 29%.

[0059] Comparative Example 1

[0060] SPEEK was prepared in the same manner as in Example 1.

[0061] Weigh 0.2 g of SPEEK and dissolve it in 8 ml of DMSO to form a uniform mixed solution. Add the mixed solution dropwise onto a flat glass plate and place it in an oven at 60° C. to dry for 24 hours to obtain SPEEK / SHPBI-0%.

[0062] The mechanical strength of the prepared PEM in the wet state is 21.5 MPa, the swelling degree is 14% at 80 °C, and the conductivity is 39 mS cm -1 The remaining weight after treatment with Fenton's reagent was 93.2% (oxidation stability); the prepared PEM was made into a membrane electrode (anode catalyst: IrO2, cathode catalyst: Pt / C), and the PEM water electrolysis test was carried out (40°C, electrolyte: pure water), and the efficiency of hydrogen production by water electrolysis reached 30%.

[0063] Comparative Example 2

[0064] SPEEK was prepared in the same manner as in Example 1.

[0065] 0.18 g of SPEEK and 0.02 g of silica nanoparticles were weighed and dissolved in 8 ml of DMSO to form a uniform mixed solution. The mixed solution was dropped onto a flat glass plate and dried in an oven at 60° C. for 24 h to obtain SPEEK / SiO2-10%.

[0066] The prepared silica-doped PEM has a mechanical strength of 32.5 MPa in a wet state, a swelling degree of 8% at 80 °C, and an electrical conductivity of 18 mS cm -1 The remaining weight after treatment with Fenton's reagent was 92.9% (oxidation stability); the prepared PEM was made into a membrane electrode (anode catalyst: IrO2, cathode catalyst: Pt / C), and a PEM water electrolysis test was carried out (40°C, electrolyte: pure water), and the efficiency of hydrogen production by water electrolysis was 27%.

[0067] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable technicians familiar with this technology to understand the content of the present invention and implement it accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A proton exchange composite membrane based on benzimidazole small molecules, characterized in that: The structural formula of the proton exchange composite membrane is shown below:

2. A method for preparing a proton exchange composite membrane based on benzimidazole small molecules according to claim 1, characterized in that: The preparation method steps are as follows: (a) Synthesis of 5,5'-bis[2-(2-hydroxy-5-sulfophenyl)benzimidazole]SHPBI Under nitrogen atmosphere, at 80°C or above, mechanical stirring is used to remove residual oxygen in polyphosphoric acid as a solvent, and then 3,3'-diaminobenzidine and 5-sulfosalicylic acid sodium dihydrate are added in sequence. After complete dissolution, the temperature is first raised to 120°C, and after reaction for 3 hours, the temperature is then raised to 150°C, and the reaction is continued for 15 hours until the reaction solution changes color. The reactant is poured into deionized water and cooled and solidified, stirred with a glass rod, and washed with deionized water by centrifugation to make the washing water neutral. Then, the remaining solid is placed in an oven for drying to obtain 5,5'-bis[2-(2-hydroxy 5-sulfophenyl)benzimidazole], which is named SHPBI; (b) Synthesis of sulfonated polyetheretherketone SPEEK The dried PEEK was dissolved in concentrated sulfuric acid and stirred at 50°C for 8 hours, then the solution was poured into an ice water bath, the precipitated SPEEK was washed with deionized water, and then vacuum dried at 60°C for 24 hours to obtain the final product SPEEK; (c) Preparation of proton exchange composite membrane based on benzimidazole small molecule SHPBI The prepared small molecule benzimidazole SHPBI and SPEEK were dissolved in a polar solvent to form a uniform mixed solution, the mixed solution was dropped onto a flat glass plate, and vacuum dried at 60° C. to form a film.

3. The method for preparing a proton exchange composite membrane based on benzimidazole small molecules according to claim 2, characterized in that: In step (a), the molar ratio of 5-sodium sulfosalicylate dihydrate to 3,3'-diaminobenzidine is greater than 2:

1.

4. The method for preparing a proton exchange composite membrane based on benzimidazole small molecules according to claim 2, characterized in that: In step (a), the amount of polyphosphoric acid used is greater than 10 times the total mass of the monomers.

5. The method for preparing a proton exchange composite membrane based on benzimidazole small molecules according to claim 2, characterized in that: In step (a), the structural formula of 5,5'-bis[2-(2-hydroxy 5-sulfophenyl)benzimidazole] is as follows:

6. The method for preparing a proton exchange composite membrane based on benzimidazole small molecules according to claim 2, characterized in that: In step (b), the mass volume ratio of PEEK to concentrated sulfuric acid is: 1 g: 10 ml.

7. The method for preparing a proton exchange composite membrane based on benzimidazole small molecules according to claim 2, characterized in that: In step (c), the doping amount of SHPBI is 5-15% of the total mass of SHPBI and SPEEK.

8. The method for preparing a proton exchange composite membrane based on benzimidazole small molecules according to claim 2, characterized in that: In step (c), the polar solvent is dimethyl sulfoxide.

9. An application of the proton exchange composite membrane based on benzimidazole small molecules according to claim 1, characterized in that: Proton exchange composite membrane based on benzimidazole small molecules is applied to water electrolysis.

Citation Information

Cited By

  • Preparation method of proton exchange membrane

    CN120127159A

  • A method for preparing a proton exchange membrane

    CN120127159B

  • Composite material filter membrane for separating waste oil and preparation method of composite material filter membrane

    CN121266387A

  • A composite material filter membrane for waste oil separation and its preparation method

    CN121266387B